Case Study : Cepat Cetak Grafik / Nurliana Nabila Abdul Rahman - Abdul Rahman, Nurliana Nabila (2020)
This case study project is one of the required assignments for the Technology Entrepreneurship (ENT600) Course aimed at learning how to be an entrepreneur that apply the technology in the business and how to manage one’s business particularly for local SME companies. Thus, Cepat Cetak Grafik is the chosen company for this case study. The goal of Cepat Cetak Grafik is to be the number one choice for the Malaysia printing company. The targets market are people around Melaka such as students and office staff. Therefore, based on an interview with Mrs. Nurathirah Shafiza Binti Azmi, the founder of Cepat Cetak Grafik, a brief overview of the company details and products is described. In addition, the company’s business, marketing and operational strategy information is also briefly explained in this report. Finally, the SWOT analysis which contained strength, weakness, opportunity and thread is discussed in the business. From the SWOT analysis, the problem face by the company is outlines and recommendation ideas to improves and solve the problem is proposed.